Elevated Red Cell Distribution Width as a Useful Marker in Neonatal Sepsis. Issue 5 (July 2021) - Bulut, Ozgul; Akcakaya, Aysimin; Bulut, Nurgul; Ovali, Fahri
Abstract : Neonatal sepsis is an important cause of neonatal morbidity and mortality in the neonatal intensive care unit. Red blood cell distribution width (RDW) is an important and independent prognostic factor in several diseases. The objective of this study was to evaluate the diagnostic value of RDW in neonatal sepsis. An observational, retrospective cohort study was conducted on newborns admitted to the neonatal intensive care unit in a Tertiary Care University Hospital between 2016 and 2019. Patients were classified into sepsis and control groups. Demographic characteristics and laboratory findings including RDW were analyzed. RDW was significantly higher in the sepsis group than in the control group ( P =0.001). RDW had an area under the receiver operating characteristic curve of 0.799 for the diagnosis of sepsis. The sensitivity and specificity of an RDW value of 17.4% were found to be 60% and 88.3%, respectively ( P =0.001). Multivariable logistic regression analysis showed a positive association of RDW with sepsis (odds ratio: 2.71; 95% confidence interval: 2.19-3.36; P =0.001). RDW value was significantly higher in neonatal sepsis and could be used as a useful alternative to other assessment tools as a readily available biomarker.